2007
DOI: 10.1007/s10802-007-9098-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the Validity and Utility of the Conners’ Continuous Performance Test in the Assessment of Inattentive and/or Hyperactive-Impulsive Behaviors in Children

Abstract: This study evaluated the validity and classification utility of the Conners' Continuous Performance Test (CCPT) in the assessment of inattentive and hyperactive-impulsive behaviors in children. Significant, positive correlations between the CCPT parameters and behavioral ratings of ADHD behaviors were hypothesized. In addition, it was hypothesized that the CCPT parameters would perform better than a random test (chance) and show fair to moderate utility of classification across the different indices. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 37 publications
3
67
1
1
Order By: Relevance
“…Despite these limitations, our results confirm that Conners' CPT has considerable potential for measuring attention problems, can distinguish ADHD from dyslexia, can distinguish both of these from clinical controls 7 and can be used as a diagnostic instrument for ADHD and LD 20 .…”
Section: Referencessupporting
confidence: 61%
“…Despite these limitations, our results confirm that Conners' CPT has considerable potential for measuring attention problems, can distinguish ADHD from dyslexia, can distinguish both of these from clinical controls 7 and can be used as a diagnostic instrument for ADHD and LD 20 .…”
Section: Referencessupporting
confidence: 61%
“…Although the CPT has marginal utility in detecting behavioral characteristics of ADHD, 34 the vast majority of studies have found the CPT to be an important and useful tool for not only demonstrating attention deficits in specific childhood disorders such as asthma 35 and fetal alcohol syndrome, 36 but also as a psychometric instrument for the detection of neural processing deficits in children with ADHD. Our current understanding suggests that in the majority of these children, seizures will remit in adolescence and they will enter adulthood seizure-free off medications.…”
Section: Statistical Analysis Baseline Neurocognitive Test Results Amentioning
confidence: 99%
“…Für die Diagnostik der ADHS wurden verschiedene Leitlinien veröffentlicht [American Academy of Child and Adolescent Psychiatry, 2007;Taylor et al, 2004;Village, 2011] [Edwards et al, 2007]. In einer Studie von Bruchmüller et al wurden 1000 zufällig ausgewählten niedergelassenen Kinder-und Jugendlichenpsychotherapeuten/-psychiatern 4 Fallvignetten zu einem Jungen bzw.…”
Section: Diagnostik In Den Verschiedenen Lebensphasenunclassified